'I can't go, I can't afford it': Financial concern amongst health students undertaking rural and remote placements during COVID‐19. (1st March 2022) - Jessup, Belinda; Hoang, Ha; Podubinski, Tegan; Obamiro, Kehinde; Bourke, Lisa; Hellwege, Barbara; Jatrana, Santosh; Heaney, Susan; Farthing, Annie; Sheepway, Lyndal; Rasiah, Rohan
Abstract: Introduction: As the coronavirus pandemic unfolded during 2020, widespread financial uncertainty emerged amongst university students across the globe. What is not yet clear is how Australian health students were financially impacted during the initial stages of the pandemic and whether this influenced their ability to undertake planned rural or remote placements. Objective: To examine (a) financial concern amongst health students during COVID‐19, (b) the financial implications of changes to planned rural or remote placements and (c) the impact of these factors on students' ability to undertake placements during the pandemic. Design: Mixed‐methods design involving an online survey ( n  = 1210) and semi‐structured interviews ( n  = 29). Nursing, medical and allied health students with a planned University Department of Rural Health‐facilitated rural or remote placement between February and October 2020 were invited to participate. Findings: 54.6% of surveyed students reported financial concern during COVID‐19. Financial concern correlated with both changes in financial position and employment, with 36.6% of students reporting a reduction in income and 43.1% of students reporting a reduction in, or cessation of regular employment. Placement changes yielded a range of financial implications. Cancelled placements saved some students travel and accommodation costs, but left others out of pocket if these expenses were prepaid. Placements that went ahead often incurred increased accommodation costs due to limited availability. Financial concern and/or financial implications of placement changes ultimately prevented some students from undertaking their rural or remote placement as planned. Discussion: Many nursing, allied health and medical students expressed financial concern during COVID‐19, associated with a loss of regular employment and income. Placement changes also presented unforeseen financial burden for students. These factors ultimately prevented some students from undertaking their planned rural or remote placement. Conclusion: Universities need to consider how best to align financially burdensome placements with the personal circumstances of students during periods of economic uncertainty.